Conductive particles, conductive material, and connection structure

CN115428097BActive Publication Date: 2026-10-16DUK SAN NEOLUX
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202180028854.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-03
Filing Date
2021-09-30
Publication Date
2026-10-16
Estimated Expiration
2041-09-30

AI Technical Summary

Benefits of technology

[0030] Furthermore, by including palladium in the form of nanoclusters inside the protrusions protruding from the conductive layer, the protrusions can be formed, and the size and height of the protrusions can be controlled according to the size of the palladium nanoclusters.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115428097B_ABST
    Figure CN115428097B_ABST
Patent Text Reader

Abstract

The present invention is characterized by: as a conductive particle including a core and a conductive layer equipped on a surface of the core and equipped with a protrusion, including palladium distributed in a first palladium region formed on a boundary surface of the conductive layer and the core and a third palladium region formed in an inner region of the protrusion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to conductive particles having a conductive layer on their core surface, and more particularly to conductive particles used as anisotropic conductive adhesive materials for connecting micro-pitch circuits. Furthermore, it relates to a conductive material utilizing said conductive particles and a connecting structure. Background Technology

[0002] Conductive materials are used in anisotropic conductive materials, such as anisotropic conductive films, anisotropic conductive adhesives, anisotropic conductive pastes, anisotropic conductive inks, and anisotropic conductive sheets, which are dispersed by mixing with curing agents, adhesives, and resin binders.

[0003] The anisotropic conductive material is used in applications such as FOG (Film on Glass), COF (Chipon Film), COG (Chip on Glass), and FOB (Film on Board).

[0004] Assuming that the anisotropic conductive material is used to bond the semiconductor chip and the flexible substrate, the anisotropic conductive material can be disposed on the flexible substrate and the semiconductor chip is stacked. Then, the anisotropic conductive material is cured under pressure / heat to form a connection structure in which conductive particles electrically connect the electrodes of the substrate and the electrodes of the semiconductor chip.

[0005] When conductive particles are used in the anisotropic conductive material, they are mixed with curing agents, adhesives, and resin adhesives. When a connection structure is formed after pressure / heating, the electrical connection between the upper and lower electrodes can be maintained by curing / bonding the anisotropic conductive material. Summary of the Invention

[0006] The present invention aims to solve the existing problems as described above. The technical problem to be achieved by the present invention is to provide a conductive particle that can form a conductive layer with a stable and uniform thickness and that can adjust the size of the protrusions formed on the conductive layer.

[0007] The conductive particles applicable to one aspect of the present invention are characterized in that:

[0008] As a conductive particle comprising a core and a conductive layer with protrusions on the surface of the core,

[0009] This includes palladium distributed in a first palladium region formed on the boundary surface between the conductive layer and the core, and palladium in a third palladium region formed inside the protrusion.

[0010] At this point, it is preferable to include a second palladium region formed within the middle of the conductive layer.

[0011] Furthermore, it is preferable that the third palladium region contains palladium nanoclusters with an average particle size of 30 nm to 130 nm.

[0012] Furthermore, it is preferable that the palladium nanoparticles in the first palladium region are more distributed than those in the surrounding area, and that the palladium nanoparticles are attached to more than 95% of the core surface area.

[0013] Furthermore, the second palladium region is an area where palladium nanoparticles are distributed more extensively than in the surrounding area.

[0014] Furthermore, it is preferable that the palladium concentration in the third palladium region is greater than that in the first palladium region or the second palladium region.

[0015] Furthermore, the conductive layer is preferably composed of one or more alloys selected from the group consisting of Ni, Sn, Ag, Cu, Pd, Zn, W, P, B, and Au.

[0016] In addition, it is preferable that the surface of the conductive layer also includes an insulating layer or insulating particles.

[0017] In addition, it is advisable to use a hydrophobic rust inhibitor to prevent rust on the outermost contour of the conductive layer.

[0018] Another aspect of the present invention relates to an anisotropic conductive material comprising the conductive particles described above.

[0019] Another aspect of the present invention relates to a connection structure comprising the conductive particles described above.

[0020] One aspect of the present invention provides a method for manufacturing conductive particles, comprising:

[0021] A) The steps involved in manufacturing a nuclear;

[0022] B) The step of forming a first palladium region by attaching palladium particles to the surface of the core;

[0023] C) The first nickel region is formed by dispersing the nucleus after step B) into the nickel plating solution;

[0024] D) The step of forming a second palladium region by injecting a palladium precursor solution after adding a reducing agent to the nucleus following step C);

[0025] E) The step of forming a second nickel region by implanting a nickel precursor into the second palladium region after step D);

[0026] F) The step of forming a third palladium region comprising palladium nanoclusters on a portion of the surface of the second nickel region by introducing a palladium precursor solution and a stabilizer into the nucleus; and,

[0027] G) The step of forming a third nickel region on the second nickel region and the third palladium region.

[0028] The conductive particles applicable to this invention are equipped with palladium at the boundary between the core and the conductive layer, thereby enabling the growth of elements constituting the conductive layer.

[0029] Furthermore, by including palladium inside the conductive layer, the conductive layer can be formed with a stable and uniform thickness.

[0030] Furthermore, by including palladium in the form of nanoclusters inside the protrusions protruding from the conductive layer, the protrusions can be formed, and the size and height of the protrusions can be controlled according to the size of the palladium nanoclusters.

[0031] In summary, a conductive layer can be uniformly formed with a certain thickness, and the size and height of the protrusions can be adjusted according to the conditions used, thereby easily transmitting to the oxide film of the electrode and creating highly stable conductive particles, anisotropic conductive materials, and connecting structures. Attached Figure Description

[0032] Figure 1 This is a transmission electron microscope (TEM) image of conductive particles applicable to one embodiment of the present invention.

[0033] Figure 2 This is a transmission electron microscope (TEM) image of a region of conductive particles without protruding conductive layer, which is applicable to one embodiment of the present invention.

[0034] Figure 3 This is a graph showing the results of energy dispersive X-ray spectroscopy (EDAX) analysis of the unprotruding central region of the conductive layer.

[0035] Figure 4 This is a transmission electron microscope (TEM) image of the raised region of the conductive layer of a conductive particle according to one embodiment of the present invention.

[0036] Figure 5 This is a graph showing the X-ray energy dispersive spectroscopy (EDAX) results of the raised central region.

[0037] [Symbol Explanation]

[0038] 10: First Palladium Region

[0039] 20: Second Palladium Region

[0040] 30: Third Palladium Region Detailed Implementation

[0041] Before proceeding with a detailed description of the invention, it should be understood that the terminology used in this specification is for the purpose of describing specific embodiments only and is not intended to limit the scope of the invention, which should be defined only by the appended claims. Unless otherwise stated, all technical and scientific terms used in this specification have the same meaning as commonly understood by one of ordinary skill in the art.

[0042] Throughout this specification and the claims, unless otherwise stated, the terms "comprise" and "comprises" are used to indicate the inclusion or commensuration of the mentioned object, step, or series of objects and steps, and do not exclude any other object, step, or series of objects or steps.

[0043] Furthermore, unless otherwise expressly stated to the contrary, various embodiments of the present invention may be combined with any other embodiments. In particular, any feature designated as preferred or preferred may be combined with any other feature designated as preferred or preferred, as well as multiple features. The embodiments of the present invention and their effects will now be described in detail with reference to the accompanying drawings.

[0044] <Conductive particles>

[0045] The conductive particles applicable to embodiments of the present invention are conductive particles that electrically connect the electrodes by being contained between the electrodes, at least one of the electrodes having an oxide film on its surface.

[0046] Typically, conductive particles are contained within anisotropic conductive materials and heated and extruded. During extrusion, the size of the conductive particles deforms, and they form electrical connections between electrodes by penetrating the electrodes through protrusions. The spacing between the electrodes varies depending on the size of the particles used, but is typically around 3 μm to 20 μm.

[0047] The conductive particle includes a core and a conductive layer disposed on the surface of the core and provided with protrusions.

[0048] The core used in this embodiment is not particularly limited. For example, resin particles or organic-inorganic mixed particles can be used as the core.

[0049] The resin particles are monomers such as polyurethanes, styrene, acrylates, benzenes, epoxy resins, amines, and imides, or modified monomers thereof, or copolymers obtained by polymerization of a mixture of the monomers using methods such as seed polymerization, dispersion polymerization, suspension polymerization, and emulsion polymerization.

[0050] The organic-inorganic hybrid particles are particles that simultaneously contain both organic and inorganic substances, and can be composed of core-shell, hybrid, or composite structures. In the case of a core-shell structure, the core is organic while the shell is inorganic, and vice versa. The organic substance used can be the monomer, modified monomer, or mixed monomer, while the inorganic substance can be oxides including SiO2, TiO2, Al2O3, and ZrO2; nitrides including AlN, Si3N4, TiN, and BaN; and carbides including WC, TiC, and SiC.

[0051] Methods for forming a shell include chemical coating, sol-gel method, spraying method, chemical vapor deposition (CVD), physical vapor deposition (PVD), and electroplating.

[0052] In addition, other forms can be adopted, such as dispersing inorganic particles into an organic matrix with a mixed structure, dispersing organic particles into an inorganic matrix, and dispersing organic / inorganic substances in a 50:50 ratio.

[0053] In addition, in the case of a hybrid structure, materials containing polysiloxanes or metal oxanes can be used.

[0054] The size of the nucleus is not particularly limited, but taking into account the general shape of the electrode and the surface roughness, it is preferably less than 6 μm, more preferably 1.5 μm to 5 μm, and even more preferably 1.5 to 4.5 μm.

[0055] The conductive layer can be composed of one or more elements such as P, B, Cu, Au, Ag, W, Mo, Pd, Co, and Pt on a Ni-based substrate. In this case, the conductive layer constitutes a single layer, but internally it consists of a single layer with varying concentrations of each element except Ni.

[0056] In embodiments of the present invention, Pd, one of the elements constituting the conductive layer, is distributed in a first palladium region formed at the boundary between the conductive layer and the core, a second palladium region formed in the middle interior of the conductive layer, and a third palladium region formed inside the protrusion. This does not mean that there is no palladium distribution outside the first, second, and third palladium regions, but rather that the palladium is present at a relatively high concentration in the defined palladium regions compared to other surrounding regions.

[0057] Figure 1 This is a transmission electron microscope (TEM) image of a conductive particle according to one embodiment of the present invention. In the figure, the conductive particle is illustrated according to the regions in which palladium is distributed internally, namely a first palladium region 10, a second palladium region 20, and a third palladium region 30.

[0058] The first palladium region 10 is formed within the conductive layer at the boundary with the core, in a manner containing palladium nanoparticles. This allows other particles forming the conductive layer to grow better on the palladium nanoparticles. At this point, the palladium nanoparticles adhere to more than 95% of the surface of the core, preferably more than 99%, and more preferably the entire surface.

[0059] The second palladium region 20 is formed in the middle region of the conductive layer in a manner that includes palladium nanoparticles. By redistributing palladium nanoparticles to the middle region of the conductive layer, the particles forming the conductive layer are mainly Ni particles, which are stacked in a larger thickness, thereby increasing the overall thickness of the conductive layer.

[0060] The third palladium region 30 is the area where palladium is distributed within the protrusion region, and it is also the region where palladium is most widely distributed. This third palladium region contains palladium nanoclusters, which are distributed within the conductive layer and serve to perform the nucleation function of the protrusions. Protrusions are formed on the conductive layer by allowing Ni particles, which form the conductive layer, to bind to their top. In this case, the particle size of the palladium nanoclusters is preferably 30 nm to 130 nm. If the size is less than this range, the protrusion formation function may not be possible due to the nanoclusters being too small; if the size is greater than this range, the protrusions may become too large or may not form uniformly.

[0061] In summary, the conductive layer is a polycrystalline material formed by growing Ni, Pd, P, B, Cu, Au, Ag, W, Mo, Co, and Pt particles.

[0062] The conductive layer thickness of the conductive particles is preferably around 30–300 nm. If the conductive layer is too thin, it will lead to an increase in resistance; if it is too thick, even a slight deformation of the conductive particles under the heating / pressurization bonding conditions of anisotropic conductive materials can cause the conductive layer to peel off from the core, resulting in decreased product reliability. A preferred thickness is 80–200 nm.

[0063] The conductive layer on the surface of the conductive particles may also contain precious metals such as gold, silver, platinum, and palladium. This can improve the conductivity of the conductive particles and achieve an anti-oxidation effect. The method of forming the surface layer is not particularly limited, and common known techniques such as sputtering, electroplating, and vapor deposition can be used.

[0064] The protrusion shape of the conductive particles is not particularly limited; it can be spherical, elliptical, or a cluster of multiple particles. The most preferred protrusion shape is a mountain shape.

[0065] The size of the protrusion is not specifically limited, but a protrusion size of 50–500 nm is preferred. When the size of the protrusion is too small or too large, it will lead to a weakening of the penetration effect on the metal oxide layer and the adhesive resin. Therefore, the preferred size of the protrusion is 100–300 nm.

[0066] The method for manufacturing conductive particles applicable to embodiments of the present invention is not particularly limited. For example, a conductive layer and protrusions can be formed by electroless gold plating after coating a catalyst material onto the surface of the nuclear resin particles. However, in order to create the required concentration gradient when forming the conductive layer, it is preferable to introduce the elements in multiple stages while changing the element concentration.

[0067] It is preferable to form an insulating layer on the outermost periphery of the conductive particles in embodiments of the present invention. With the miniaturization and increased integration of electronic products, the spacing between electrodes will become smaller. Therefore, in the absence of insulating particles on the outermost periphery, electrical conductivity with adjacent electrodes may occur.

[0068] Methods for forming an insulating layer include methods that utilize functional groups to chemically attach insulating particles to the outermost contour of conductive particles, and methods that apply the coating by spraying or impregnation after dissolving the insulating solution in a solvent.

[0069] It is preferable to perform rust prevention treatment on the conductive layer of the conductive particles of the present invention. This is because rust prevention treatment can increase the contact angle with water and thereby improve reliability in high humidity environments, and can also reduce the performance degradation of connecting parts caused by impurities dissolving in water. Therefore, it is preferable to use hydrophobic rust inhibitors such as phosphate esters or salts thereof containing phosphoric acid, alkoxysilanes containing silanes, alkyl thiols containing thiols, and dialkyl disulfides containing sulfides.

[0070] After the rust inhibitor is dissolved in the solvent, methods such as dipping and spraying can be used.

[0071] The size of the conductive particles is not particularly limited, but is preferably 6 μm or less. More preferably, it is 5 μm or less. This is because the electrode spacing at the application site of the anisotropic conductive material manufactured using the conductive particles of the present invention is very small, so it is almost never used to be larger than 6 μm.

[0072] <Methods for Manufacturing Conductive Particles>

[0073] The method for manufacturing conductive particles according to embodiments of the present invention may include a nucleus dispersion step S1, a conductive layer forming step S2 with protrusions, and a rust prevention step S3, wherein the rust prevention step S3 may be optionally included.

[0074] At this point, the nuclear dispersion step S1 includes the nuclear particle synthesis step S1a and the gold-plated catalyst activation step S1b.

[0075] First, in the nuclear particle synthesis step S1a, copolymers are produced by polymerization of monomers such as polyurethanes, styrene, acrylates, benzenes, epoxy compounds, amines, and imides, or modified monomers thereof, or mixtures of such monomers, through methods such as seed polymerization, dispersion polymerization, suspension polymerization, and emulsion polymerization.

[0076] When the organic-inorganic hybrid particles employ a core-shell structure, the core is organic and the shell is inorganic, and vice versa. The organic material used can be the monomer, modified monomer, or mixed monomer, while the inorganic material can be oxides including SiO2, TiO2, Al2O3, and ZrO2; nitrides including AlN, Si3N4, TiN, and BaN; and carbides including WC, TiC, and SiC.

[0077] Methods for forming a shell include chemical coating, sol-gel method, spraying method, chemical vapor deposition (CVD), physical vapor deposition (PVD), and electroplating.

[0078] In addition, it is also possible to use the form of dispersing inorganic particles into an organic matrix, the form of dispersing organic particles into an inorganic matrix, and the form of dispersing organic and inorganic substances in a 50:50 ratio.

[0079] In one example, the organic material is dispersed in a solution containing a solvent and a polymerization initiator using ethoxylated triacrylate monomers and ethoxylated diacrylate monomers. The dispersion process may include homogenization using an ultrasonic homogenizer.

[0080] Furthermore, nuclear resin microparticles are formed by adding a solution containing a dispersant stabilizer and a surfactant to the dispersion treatment liquid and performing polymerization engineering treatment under heated conditions.

[0081] Next, in the gold-plated catalyst activation step S1b, the nuclear particles produced in step S1a are activated using an electroless gold-plated catalyst.

[0082] Specifically, in the gold-plated catalyst activation step S1b, after the nuclei are treated with a surfactant, they are pretreated using various known methods for sensitizing the electroless gold-plated catalyst. Next, the sensitized nuclei are added to a solution containing the precursor of the electroless metal gold-plated catalyst and activation is performed.

[0083] By accelerating the process by immersing the activated nuclei in a solution containing a strong acid and stirring at room temperature, nuclei treated with an electroless gold plating catalyst can be obtained. Palladium is preferably used as the electroless gold plating catalyst, and the catalyst-treated palladium will form a first palladium region.

[0084] Next, the step S2 of forming a raised conductive layer includes a core dispersion step S2a and a raised conductive layer forming step S2b.

[0085] In the nucleus dispersion step S2a, the nucleus is placed into a nickel-based alloy gold plating solution for dispersion, thereby depositing nickel ions on the surface of the nucleus with the nickel-based gold plating solution and thereby forming a first nickel region.

[0086] At this point, the nickel-based alloy gold plating solution is manufactured by sequentially dissolving the precursor of nickel alloy elements, complexing agent, lactic acid, stabilizer and surfactant. After the catalytically treated nuclei obtained in step S1b are added to the manufactured gold plating solution, dispersion treatment is performed using an ultrasonic homogenizer.

[0087] To improve the adhesion and dispersibility between the insulating particles and the conductive layer during the initial Ni reduction reaction in the conductive layer formation step S2b described later, it is advisable to adjust the pH of the dispersion solution to 5.5–6.5 using a solution such as ammonia. While good adhesion and dispersibility are achieved at pH values ​​below 4, the low reactivity may result in some particles not being plated with gold. Conversely, at pH values ​​above 6.5, abnormal Ni precipitation may cause the formed conductive layer surface to become loose, leading to poor adhesion and dispersibility.

[0088] Step S2b, which forms the raised conductive layer, is a step in which the raised conductive layer is formed simultaneously with the injection of the nickel precursor solution and the palladium precursor solution.

[0089] After the nucleus dispersion step S2a, a reducing agent is added to the nucleus on which the first nickel region is formed on the surface, and then a second palladium region is formed by injecting a palladium precursor solution.

[0090] The thickness of the conductive layer is increased by further forming a second nickel region by incorporating a nickel precursor into the second palladium region.

[0091] Next, a palladium precursor solution and a stabilizer are added again to the surface of the second nickel region, thereby forming a third palladium region in a portion of the surface. At this point, palladium nanoparticles will form clusters in the third palladium region, becoming larger than individual nanoparticles, and will form within a portion of the second nickel region.

[0092] In this way, the surface will be divided into a second nickel region and a third palladium region. When the nickel precursor solution is poured into each of the upper parts again, nickel will be formed on the upper part of the second nickel region and the upper part of the third palladium region, thereby forming a third nickel region that thickens the conductive layer while forming protrusions.

[0093] That is, it is estimated that the mechanism for forming protrusions in the manufacturing method described above is as follows: When a reducing agent and a Ni aqueous solution are added to the gold plating solution, nickel particles are simultaneously and multiple times generated under the action of the reducing agent, thereby allowing the nickel particles to adhere to the surface of the microparticles and form a first nickel region. In order to form a thicker gold plating layer, Pd particles are attached above the first nickel region by adding a low concentration of Pd precursor solution, while the reduced nickel nanoparticles form a second nickel region. Next, in order to form protrusions, larger Pd clusters are formed by adding a high concentration of Pd precursor solution and a stabilizer, at which point the palladium nanoclusters act as nuclei in the protrusion formation. Next, nickel covers the surface by adding a Ni precursor solution and a reducing agent, thereby forming a conductive layer equipped with protrusions where the palladium nanoclusters are partially raised.

[0094] Furthermore, when forming the conductive layer, a raised conductive layer with a concentration gradient of each element can be formed by repeatedly adding a solution containing a precursor of at least one element selected from the group consisting of P, B, Cu, Au, Ag, W, Mo, Pd, Co, and Pt.

[0095] As an example, one or more precursors selected from P and B can be added in the core dispersion step S2a, and alloying elements containing one or more elements selected from Cu, Au, Ag, W, Mo, Pd, Co and Pt can be added in stages in the conductive layer formation step S2b, thereby forming a conductive layer with a concentration gradient and protrusions.

[0096] At this point, the alloying elements can be added in 2 to 5 batches at intervals of 10 to 30 minutes, or in 2 to 4 batches at intervals of 15 to 25 minutes. The amount added can be gradually increased in batches, or it can be added continuously as needed. In order to gradually increase the concentration towards the convex side, it is advisable to gradually increase the amount added according to the addition speed over a certain period of time.

[0097] The selectively performed rust prevention step S3 can be performed by introducing conductive particles into the rust inhibitor solution, but is not limited to this.

[0098] As the rust inhibitor solution, hydrophobic rust inhibitors such as phosphate esters or their salts containing phosphoric acid, alkoxysilanes containing silanes, alkyl thiols containing thiols, and dialkyl disulfides containing sulfides can be used. Electroless nickel rust inhibitors, including product name SG-1 sold by MSC Corporation, can also be used.

[0099] After the conductive particles are introduced, processes such as ultrasonic treatment can be performed.

[0100] <Anisotropic conductive materials>

[0101] This invention manufactures anisotropic conductive materials by dispersing conductive particles into an adhesive resin. Examples of anisotropic conductive materials include anisotropic conductive slurries, anisotropic conductive films, and anisotropic conductive sheets.

[0102] The resin adhesive is not specifically limited. For example, vinyl resins such as styrene, acrylic, and vinyl acetate, thermoplastic resins such as polyolefins and polyamides, and curable resins such as polyurethane and epoxy resins can be used. The resin can be used alone or in combination with two or more.

[0103] To achieve polymerization or curing, free radical initiators such as benzoyl peroxide (BPOL), photoinitiators such as trimethylbenzoylphenylphosphinate (TPO), and epoxy resin latent curing agents such as HX3941HP can be used alone or in combination.

[0104] Furthermore, other substances can be added to the anisotropic conductive adhesive resin without hindering the achievement of the objectives of this invention. For example, colorants, softeners, heat stabilizers, light stabilizers, antioxidants, and inorganic particles can be added.

[0105] The manufacturing method of the anisotropic conductive material is not particularly limited. For example, it can be used as an anisotropic conductive slurry by uniformly dispersing conductive particles into a resin binder, or it can be used as an anisotropic film by thinly coating it onto release paper.

[0106] <Connection Structure>

[0107] The connection structure applicable to embodiments of the present invention is a connection structure that connects circuit boards between circuit boards using conductive particles or anisotropic conductive materials applicable to embodiments of the present invention. For example, it can be used to connect semiconductor chips in a smartphone display to glass substrates constituting circuits, or to connect flexible substrates constituting circuits, and can also be used as a method for connecting μ-LEDs and mini-LEDs to circuit boards.

[0108] The connection structure of the present invention will not cause the circuit to malfunction due to poor contact or a sharp increase in resistance.

[0109] The present invention will now be described in detail through specific and diverse embodiments, but this is only to help understand the present invention, and the technical concept of the present invention is not limited thereto.

[0110] [Example]

[0111] Example 1

[0112] 1) Manufacturing of nuclear resin microparticles S1a

[0113] The first solution was prepared by adding 800g of trimethylolpropane ethoxylate triacrylate (TMPETA), 50g of 1,6-hexanediol ethoxylate diacrylate (HDEDA), and 800g of divinylbenzene (DVB) to a 3L glass beaker, along with 5g of benzoyl peroxide (BPO) as an initiator. The solution was then treated in an ultrasonic bath at 40kHz for 10 minutes.

[0114] A second solution was prepared by adding 4,000 g of deionized water, 500 g of dispersant stabilizer polyvinylpyrrolidone (PVP)-30K, and surfactant sodium dioctyl sulfosuccinate (Solusol) to a 5 L polypropylene (PP) beaker.

[0115] The first and second solutions were added to a 50L reactor along with 41,000g of deionized water. The mixture was then treated with an ultrasonic homogenizer (20kHz, 600W) for 90 minutes, while simultaneously heating to 85°C at 120rpm. After reaching 85°C, the solution was maintained at this temperature for 16 hours to perform polymerization processing.

[0116] Nucleated resin microparticles were obtained by performing filtration, washing, grading, and drying processes on the polymerized microparticles. The average diameter of the manufactured nucleated resin microparticles was determined using the mode value measured with a laser particle size analyzer (BECKMAN MULTISIZER TM3). The number of nucleated microparticles measured was 75,000. Their average particle size was 3.02 μm.

[0117] 2) Catalyst processing engineering S1b

[0118] 30g of the manufactured nuclear resin microparticles were placed in a solution containing 800g of deionized water and 1g of surfactant Triton X100 and treated in an ultrasonic bath for 1 hour to remove excess unreacted monomers and oily components from the nuclear resin microparticles. At the end of the washing and degreasing process, three rinses were performed using deionized water at 40°C.

[0119] Next, the Pd catalyst treatment was performed. After dissolving 150g of stannous chloride and 300g of 35-37% hydrochloric acid in 600g of deionized water, the washed and degreased nuclear resin particles were added, and sensitization treatment was performed by impregnation and stirring at 30°C for 30 minutes, followed by three water washes.

[0120] Sensitized nuclear resin microparticles, 1g of palladium chloride, and 200g of 35-37% hydrochloric acid were added to 600g of deionized water and activated at 40°C for 1 hour. After activation, three water washing processes were performed.

[0121] The activated nuclear resin microparticles and 100g of 35-37% hydrochloric acid were added to a solution of 600g of deionized water and stirred at room temperature for 10 minutes to perform accelerated treatment. After accelerated treatment, the microparticles were washed three times with water to obtain nuclear resin microparticles without electrolytic gold plating catalyst treatment.

[0122] 3) Nuclear dispersion S2a

[0123] In a 5L reactor, 3,200g of deionized water was added, and 260g of nickel sulfate (Ni salt), 5g of sodium acetate (complexing agent), 2g of lactic acid, 0.001g of Pb-acetate (stabilizer), 0.001g of sodium thiosulfate (stabilizer), and 0.03g of Triton 80 (anti-agglomeration agent) were dissolved sequentially to produce gold plating solution a. The catalyst-treated nuclear resin microparticles were added to solution a, and the mixture was dispersed using an ultrasonic homogenizer for 10 minutes. After dispersion, the pH of the solution was adjusted to 5.5 using ammonia water to produce solution b.

[0124] 4) Formation of a raised conductive layer S2b

[0125] Solution c is prepared by dissolving 350g of deionized water and 200g of sodium hypophosphite as a reducing agent in a 1L beaker.

[0126] Solution d is prepared by dissolving 250g of deionized water, 100g of nickel sulfate, and 10g of hydrochloric acid in a 1L beaker.

[0127] Solution e is prepared by dissolving 100g of deionized water, 0.005g of PdCl2, and 10g of hydrochloric acid in a 1L beaker.

[0128] Solution f is prepared by dissolving 400g of deionized water and 300g of sodium hypophosphite as a reducing agent in a 1L beaker.

[0129] Solution g was prepared by dissolving 100 g of deionized water, 0.05 g of PdCl2, 30 g of hydrochloric acid, Triton X-100 as a stabilizer, and 10 g of sodium hypophosphite in a 1 L beaker.

[0130] Solution h was prepared by dissolving 200g of deionized water and 150g of sodium hypophosphite as a reducing agent in a 1L beaker.

[0131] Solution i is prepared by dissolving 150g of deionized water, 50g of nickel sulfate, and 10g of hydrochloric acid in a 1L beaker.

[0132] While maintaining the temperature of the 5L reactor (solution b-1) at 55°C, solution c is added at a rate of 10g per minute using a metering pump, and the temperature of the reactor is heated and maintained at 75°C for 35 minutes.

[0133] After adding solution c, maintain for 10 minutes, then add solution e and maintain for 5 minutes. Then, simultaneously add solutions d and f using a metering pump at a rate of 10g per minute.

[0134] After adding solutions d and f, maintain for 10 minutes, then maintain until clusters form after adding solution g.

[0135] After adding solution g, maintain for 10 minutes. Then, add solutions h and i using a metering pump at a rate of 10g per minute.

[0136] After adding solutions h and i, maintain the solution for 10 minutes to obtain Ni-plated gold-coated protruding conductive particles.

[0137] Comparative Example 1

[0138] The solution c in Example 1 was changed to 200g of deionized water and 150g of sodium hypophosphite as a reducing agent. After gold plating, a crushing process was performed to eliminate the aggregation of conductive particles. Next, a solution d was prepared, consisting of 200g of deionized water, 150g of sodium hypophosphite as a reducing agent, 10g of Triton X-100 as a protrusion forming agent, and 0.05g of sodium citrate as a stabilizer. Then, the process was performed using a metering pump in the same manner as in Example 1.

[0139] [Experimental Example]

[0140] Experimental Example 1

[0141] exist Figure 2 The figure shows a transmission electron microscope (TEM) image of the region without protruding conductive layer of the conductive particles in Example 1. This confirms that the second palladium region, where palladium is distributed in the central region without protruding conductive layer, appears as a brighter area.

[0142] also, Figure 3 The X-ray energy dispersive spectroscopy (EDAX) results of the middle region of the non-protruding area of ​​the conductive layer confirm that Ni is distributed throughout the conductive layer, but there is a second palladium region in the middle region.

[0143] Experimental Example 2

[0144] exist Figure 4 The figure shows a transmission electron microscope (TEM) image of the raised region of the conductive layer of the conductive particles in Example 1. This confirms that the third palladium region, where palladium is distributed in the middle region of the conductive layer, appears as a brighter area.

[0145] also, Figure 5 The X-ray energy dispersive spectroscopy (EDAX) analysis results of the central region of the protrusion confirm that there is a third palladium region with palladium nanoclusters distributed in the center of the protrusion.

[0146] exist Figure 2The figure shows a transmission electron microscope-X-ray energy dispersive spectroscopy (TEM-EDAX) image of the conductive particles applicable to Example 1, which confirms that there is no Pd or only a very small amount of Pd in ​​the non-protruding areas of the conductive layer.

[0147] The features, structures, and effects illustrated in the various embodiments described above can be implemented by those skilled in the art in combination with or by modification of other embodiments. Therefore, any content relating to the combinations and modifications described above should also be construed as being included within the scope of this invention.

Claims

1. A type of conductive particle, As a conductive particle comprising a core and a conductive layer disposed on the surface of the core and having protrusions thereof, it includes: A first palladium region formed at the boundary between the conductive layer and the core, in a manner that includes palladium nanoparticles; A second palladium region formed in the middle region of the conductive layer in a manner incorporating palladium nanoparticles; and Palladium is distributed in a third palladium region within the protrusion, wherein the third palladium region contains palladium nanoclusters; The conductive layer with protrusions consists of a nickel-based monolayer.

2. The conductive particles according to claim 1, The palladium nanoclusters contained in the third palladium region have an average particle size of 30 nm to 130 nm.

3. The conductive particles according to claim 1, The palladium nanoparticles in the first palladium region are more abundant than those in the surrounding area, and the palladium nanoparticles are attached to more than 95% of the core surface area.

4. The conductive particles according to claim 1, The second palladium region is the area where palladium nanoparticles are more distributed compared to the surrounding area.

5. The conductive particles according to claim 1, The palladium concentration in the third palladium region is greater than the palladium concentration in the first palladium region or the second palladium region.

6. The conductive particles according to claim 5, The conductive layer further includes one or more alloys selected from the group consisting of Sn, Ag, Cu, Pd, Zn, W, P, B and Au.

7. The conductive particles according to claim 6, The surface of the conductive layer also includes an insulating layer or insulating particles.

8. The conductive particles according to claim 7, The outermost contour of the conductive layer is treated with a hydrophobic rust inhibitor for rust prevention.

9. An anisotropic conductive material, It includes conductive particles according to any one of claims 1 to 8.

10. A connection structure, It includes conductive particles according to any one of claims 1 to 8.

11. A method for manufacturing conductive particles having a raised conductive layer, comprising: A) The steps involved in manufacturing a nuclear; B) The step of forming a first palladium region by attaching palladium particles to the surface of the core; C) The step of forming a first nickel region by dispersing the nucleus after step B) into the nickel plating solution; D) The step of forming a second palladium region by injecting a palladium precursor solution after the nucleus is introduced into the nucleus following step C); E) The step of forming a second nickel region by implanting a nickel precursor into the second palladium region after step D); F) The step of forming a third palladium region containing palladium nanoclusters in a portion of the surface of the second nickel region by introducing a palladium precursor solution and a stabilizer into the nucleus; as well as, G) The step of forming a third nickel region on the second nickel region and the third palladium region. The conductive particles include: A first palladium region formed at the boundary between the conductive layer and the core, in a manner that includes palladium nanoparticles; A second palladium region formed in the middle region of the conductive layer in a manner incorporating palladium nanoparticles; and Palladium is distributed in a third palladium region within the protrusion, wherein the third palladium region contains palladium nanoclusters; The conductive layer with protrusions consists of a nickel-based monolayer.

Citation Information

Patent Citations

  • Conducting particles, anisotropic electric conductivity bonding agent membrane and connection structure body

    CN204651018U